Analysis of the marketing activities of the INEX-SDA non-profit organization - Zusková, Michaela (2016)
Non-profit organizations are an integral part of the Czech economy and important partner for the government. In today's economic environment, NGOs face increasing competition not only from other similar institutions, but also from for-profit oriented companies. They are, therefore, forced to adopt entrepreneurial marketing techniques in order to succeed in the market. The aim of this Master Thesis is to analyze the non-governmental, non-profit organization INEX-SDA including its marketing strategies, to interpret the results based on marketing theory and to suggest possible improvements that could lead to better public awareness of the chosen organization.